1975
DOI: 10.1044/jshd.4001.84
|View full text |Cite
|
Sign up to set email alerts
|

Relative Intelligibility of the CID Spondees as Presented Via Monitored Live Voice

Abstract: Using three speakers and 75 subjects, a 7.90dB range in the relative intelligibility of the Central Institute for the Deaf (CID) spondees was found when they were presented via monitored live voice. This range is consistent with previous research and is considered unnecessarily large and detrimental to the efficiency and precision of the speech reception threshold (SRT) test. The exclusive use of 18 words that have a mean range of 1.5 dB is suggested. The slope of the 3l-item spondee articulation function is 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

1980
1980
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
10
0
2
Order By: Relevance
“…The means for the slopes from 20 to 80% for the Mandarin trisyllabic psychometric functions, for both the male and the female talker, are in close agreement with means for SRT materials that have been reported in other languages. The mean slope for English spondaic words has generally been reported between 7.2%/dB and 10%/dB (Hudgins et al, 1947;Hirsh et al, 1952;Young et al, 1982;Wilson & Strouse, 1999), or going as high as 12%/dB (Beattie et al, 1975;Ramkissoon, 2001). In other languages, the mean slopes have also been similar to those found in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The means for the slopes from 20 to 80% for the Mandarin trisyllabic psychometric functions, for both the male and the female talker, are in close agreement with means for SRT materials that have been reported in other languages. The mean slope for English spondaic words has generally been reported between 7.2%/dB and 10%/dB (Hudgins et al, 1947;Hirsh et al, 1952;Young et al, 1982;Wilson & Strouse, 1999), or going as high as 12%/dB (Beattie et al, 1975;Ramkissoon, 2001). In other languages, the mean slopes have also been similar to those found in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The mean slope for English spondaic words has generally been reported between 7.2 %/dB and 10 %/dB (Hudgins et al, 1947;Hirsh et al, 1952;Young et al, 1982;Wilson & Strouse, 1999), going as high as 12 %/dB (Beattie et al, 1975;Ramkissoon, 2001). In other languages the mean slopes have also been similar to those found in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The validity and reliability of speech audiometry testing may be affected by a number of factors including the number of words included in the list (Resnick, 1962;Grubb, 1963), word selection and homogeneity (Luce, 1986;Cambron et al, 1991;Wilson & Carter, 2001), accent of the talker (Weisleder & Hodgson, 1989), method and level of presentation (Beattie et al, 1975;Hood & Poole, 1980;Pisoni, 1985), as well as type of recording (Kamm et al, 1980;Ridgway, 1986). Several studies have also found differences in speech audiometry results in hearing-impaired populations due to talker gender (Davis & Davidson, 1996;Stelmachowicz et al, 2002).…”
Section: Sumariomentioning
confidence: 98%
“…A number of factors have been identified which can influence the validity and reliability of speech discrimination testing, including word selection and homogeneity (Brandy, 1966;Kreul et al, 1969;Hood & Poole, 1980;Luce, 1986;Cambron et al, 1991;Wilson & Carter, 2001), dialect of the talker and lexical neighborhood (Luce, 1986), number of words included in the list (Elpern, 1961;Resnick, 1962;Grubb, 1963a;Grubb, 1963b), and method and level of presentation (Campbell, 1965;Brandy, 1966;Creston et al, 1966;Beattie et al, 1975;Hood & Poole, 1980;Pisoni, 1985), as well as type of recording (Kamm et al, 1980;Ridgway, 1986). There have been a number of studies which have documented differences in speech discrimination due to talker gender in hearing-impaired populations (Davis & Davidson, 1996;Stelmachowicz et al, 2002).…”
Section: Sumariomentioning
confidence: 98%